Microquimerismo em glândulas salivares labiais de pacientes submetidas a transplante de células tronco hematopoiéticas - Leandro Napier de Souza (2010)
OBJECTIVE: Microchimerism represents a small portion of cells or DNA from one individual in another one. It has been extensively investigated in autoimmune diseases, which display similarities with graft-versus-host disease. The aim of this study was to investigate the presence of microchimerism in minor salivary glands of hematopoietic stem cell transplanted patients, one of the targets of graft-versus-host disease. METHODS: Labial salivary glands biopsy specimens from 11 stem cell transplanted patients were analyzed. The samples were grouped in control (5 specimens from a female-to-female transplantation) and study group (5 glands from male-to-female transplantation). One male transplanted patient was used as a positive control. Fluorescence in-situ hybridization with Y-chromosome probe and immunofluorescence anticytokeratin AE1/AE3 were used to identify Y-chromosome positive glandular epithelial cells from these patients who have received allogeneic hematopoietic stem cell transplantation. RESULTS: All samples were positive to Y-chromosome and cytokeratin AE1/AE3, in agreement with the pattern exhibited by male labial salivary gland. None of the samples from control group (female-to-female transplantation) were positive to Y-chromosome despite being positive to cytokeratin AE1/AE3. CONCLUSION: Microchimerism in the labial salivary glands of sex-mismatched stem cell transplanted patients is a real phenomenon. Further studies are necessary to elucidate the impact of this phenomenon on the clinical status of stem cell transplanted patients.